Measurement of inner wall limiter SOL widths in KSTAR tokamak. (August 2017) - Bak, J.G.; Pitts, R.A.; Kim, H.S.; Lee, H.H.; Bin, C.; Juhn, J.W.; Hong, S.H.; Garcia, O.E.; Kube, R.A.; Seo, D.C.
Abstract: Scrape-off layer (SOL) widths λq are presented from the KSTAR tokamak using fast reciprocating Langmuir probe assembly (FRLPA) measurements at the outboard mid-plane (OMP) and the infra-Red (IR) thermography at inboard limiter tiles in moderately elongated ( κ  = 1.45 – 1.55)L -mode inner wall-limited (IWL) plasmas under experimental conditions such as BT  = 2.0 T, PNBI  = 1.4 – 1.5 MW, line averaged densities 2.5 – 5.1 × 10 19  m −3 and plasma current Ip  = 0.4 − 0.7 MA. There is clear evidence for a double exponential structure in q|| (r) from the FRLPA such that, for example at Ip  = 0.6 MA, a narrow feature, λq, near (=3.5 mm) is found close to the LFCS, followed by a broader width, λq, main (=57.0 mm). Double exponential profiles ( λq, near  = 1.5 – 2.8 mm, λq, main  = 17.0 – 35.0 mm) can be also observed in the IR heat flux mapped to the OMP throughout the range of Ip investigated. In addition, analysis of SOL turbulence statistics obtained with the FRLPA shows high relative fluctuation levels and positively skewed distributions in electron temperature and ion particle flux across the SOL, with both properties increasing for longer distance from the LCFS, as often previously observed in the tokamaks. Interestingly, the fluctuation character expressed in terms of spectral distributions remains unchanged in passing from the narrow to the broad SOL heat flux channel.